Síntese e caracterização de vidros cálcioboroteluretos codopados com Er3+E Yb3+ - SILVA, Rachel de Andrade Avelar da (2018)
In this study, Er3+/Yb3+ codoped Calcium-Borotellurite glasses were synthesized and characterized. Structural (X-ray diffraction, volumetric density, molar volume, Raman spectroscopy, Fourier transform infrared-FTIR spectroscopy), thermal (differential thermal analysis -DTA and specific heat), optical and spectroscopic (refraction index, Optical absorption, luminescence and a radiative lifetime at room temperature, luminescence and a radiative lifetime as a function of temperature) properties were investigated as a function of Yb3+ content. The samples were prepared by melt-quenching technique, following the composition: 70 TeO2 - 17,0 B2O3 – 7,0 CaF2 – (5,5-x) CaO – 0,5 Er2 O3 – xYb2O3 (x= 0; 1; 2; 3 and 5 wt%). The glasses were successfully synthesized and the amorphous character of samples confirmed by X-ray diffraction. The values of density, molar volume and refractive index increased as a function of Yb2O3 content. The Raman, FTIR and DTA results confirm the structural change of the glasses with incorporation of Yb3+. The spectra Raman and FTIR show the presence TeO4, TeO3, TeO3+1, BO4, BO3 and non-bridging oxygens in the structure of glasses. The glass transition temperature (Tg) and specific heat of the samples decreased with insertion of Yb3+. The optical absorption bands showed characteristic transitions of Er3+ and Yb3+. The luminescence results show an increase of intensities at ~1535 nm as a function of Yb3+ content, due to energy transfer between Yb3+ and Er3+ ions. The values radiative lifetime values decreased with increase of Yb3+ due to cross-relaxation between doping ions. The emission intensity at ~1535 nm decreased with the increase of temperature from 300 to 420 K. The calcium borotellurite glasses codoped with Er3+/Yb3+ presented attractive properties for aplications as optical fiber, optical amplifiers or other photonic devices, such as high refraction index and high emission intensity at ~1535 nm,.